Helen Keller : autobiographies & other writings : the story of my life : the world I live in : essays, speeches, letters & journals - Keller, Helen, 1880-1968 (Library of America, 2024)
"A deluxe hardcover edition of Keller's classic memoir The Story of My Life--presented in complete and unredacted form--along with the brilliant, still-underappreciated personal essays of The World I Live In, in which Keller reflects on the senses, language, philosophy, dreams, and belief. Includes a selection of more than a dozen essays, speeches, and letters--most of them out-of-print, previously uncollected, or previously unpublished--revealing Keller's thoughts on religion and faith, women's rights and workers' rights, racial injustice, and the peace movement. Chapters from her later memoir Midstream recall her friendship with Mark Twain, and memories of her mother"--